2012
DOI: 10.3174/ajnr.a3224
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Experience with the Pipeline Embolization Device for Repair of Unruptured Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE: Flow-diverting stents, such as the PED, have emerged as a novel means of treating complex intracranial aneurysms. This retrospective analysis of the initial Canadian experience provides insight into technical challenges, clinical and radiographic outcomes, and complication rates after the use of flow-diverting stents for unruptured aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 23 publications
5
103
1
4
Order By: Relevance
“…3,6 Even in flow diversion, cases of thromboembolism due to in-stent thrombosis or delayed migration of the device, distal parenchymal hemorrhage, or aneurysm rupture due to degradation of the aneurysmal wall or endoleak have been reported. 4,[7][8][9][10][11][12] A meta-analysis by Brinjikji et al, 13 including 1451 patients with 1654 aneurysms, found procedure-related morbidity and mortality rates for flow diversion of 5% and 4%, respectively. The authors concluded that the procedure-related risk with flow diverters is not negligible and should be taken into account when considering the best therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Even in flow diversion, cases of thromboembolism due to in-stent thrombosis or delayed migration of the device, distal parenchymal hemorrhage, or aneurysm rupture due to degradation of the aneurysmal wall or endoleak have been reported. 4,[7][8][9][10][11][12] A meta-analysis by Brinjikji et al, 13 including 1451 patients with 1654 aneurysms, found procedure-related morbidity and mortality rates for flow diversion of 5% and 4%, respectively. The authors concluded that the procedure-related risk with flow diverters is not negligible and should be taken into account when considering the best therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, their users experienced neither the complications of device migration nor incomplete neck coverage due to device shortening as reported in early series. 10,12 We believe that these structural improvements combined with extensive operator expertise (both of our operators had practiced the delivery and deployment of the Tubridge on models and gained full knowledge of the Tubridge characteristics before placing it in humans) reduced the chance of technical adverse events in patients treated with FD.…”
Section: Characteristics and Feasibility Of Tubridge Flow Divertersmentioning
confidence: 99%
“…These results are comparable with those reported in other FD series; technical adverse events rates for the Pipeline and Silk flow diverters have been reported as 2.3%-13% and 12.3%-23.1%, respectively. 10,[12][13][14][15][16][17][18][19][20][21][22][23] In theory, a flow diverter can promote healing in aneurysms without additional coiling. However, coils were introduced into the aneurismal sac simultaneously with flow diverter placement in 18 aneurysms of this series.…”
Section: Characteristics and Feasibility Of Tubridge Flow Divertersmentioning
confidence: 99%
“…[1][2][3][4][5] Speculation remains regarding the etiology of both forms of hemorrhage, with an overall hemorrhage risk of 7% in reported series. 6 Delayed parenchymal hemorrhages typically occur on the side of the treated aneurysm and at an incidence in excess of that expected due to dual antiplatelet medication alone and from that reported in prior non-flow-diverting-stent literature.…”
mentioning
confidence: 99%